Pelatihan Manajemen Keuangan Pribadi Menggunakan Microsoft Excel - Violeta Nirmala; Robi Krisna; Irian Nasri (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The fourth industrial revolution has brought about significant changes in all fields, including the financial sector. Personal finance management involves various aspects, including: 1). Budget planning (budgeting): Developing a plan for expenses and income on a regular basis. 2). Expenditure control: Regulating consumption patterns so as not to exceed income. 3). Saving and investment: Setting aside a portion of income for future needs or increasing asset value. 4). Debt management: Avoiding and/or managing debt so that it remains within repayment limits. 5). Long-term financial planning: Setting financial goals such as education, home, retirement, or emergency fund. The main goal of personal financial management is for individuals to achieve financial stability, avoid unnecessary financial risks, and have a more financially prosperous life.The implementation of community service goes well, this can be seen from the results of the completion of assignments by training participants to record personal finances using Microsoft excel and the implementation of excel formulas that can facilitate training participants in calculating the final balance. It is hoped that after this training participants can implement personal finance and financial records to be more structured and well recorded so that training participants can plan finances for a better future.